Optimization of lightweight GGBFS and FA geopolymer mortars by response surface method - Nassani, Dia Eddin; Mermerdas, Kasim; Algin, Zeynep; Oleiwi, Safie Mandi; Nassanı, Dıa Eddın (ELSEVIER SCI LTD, 2017)
In the first stage of the paper, the effect of binder content, curing temperature and curing time on the compressive strength of light-weight geopolymer mortar (LWGM) was investigated. The base materials used for LWGM are ground granulated blast furnace slag (GGBFS) and fly ash (FA). The main components of LWGM are lightweight pumice aggregate and alkali activated FA or GGBFS binder. Effectiveness of aforementioned parameters was examined in terms of variation of the compressive strengths of LWGMs. The experiments were performed on LWGM cubes under curing temperatures of 60, 80, 100 and 120 degrees C with curing period of 2, 6, 8, 24, 48 and 72 h. The alkaline activator is a mix of 12 M NaOH solution with sodium silicate in ratio of 1:2.5. The ratio of alkaline solution to binder was taken as 0.50. 7 binder contents were taken between 650 to 1250 kg/m(3) with 100 kg/m(3) increment. Full factorial experimental program was adopted to observe compressive strength development of LWGMs. Therefore, 336 data samples were obtained. The second stage of the paper is to optimize those experimental parameters through response surface method. Test results indicate that the increment in the binder content increases the compressive strength of LWGM. The strength increases with the increase of curing temperature and curing period of LWGM. The experimental verification indicated a good agreement with optimized results. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Curing regime; Geopolymer; Fly ash; Compressive strength; Lightweight mortar; Optimization